Asuhan Keperawatan Pasien Dengan Penyakit Paru Obstruksi Kronis (PPOK) Di Ruang Inap Paru RSUD Prof. H. Muhammad Yamin, SH - Olifia Darti Utama; Debby Silvia Dewi; Mike Asmaria; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Chronic Obstructive Pulmonary Disease (COPD) caused 3.23 million deaths worldwide in 2024, making it the third leading cause of death. In Indonesia, COPD accounted for 1,111 deaths, while its prevalence in West Sumatra reached 3.1% or approximately 164,000 people. This case study aimed to describe the nursing care process for a patient with COPD, including assessment, nursing diagnosis, intervention planning, implementation, evaluation, and documentation. The study involved one patient (Mr. R) who was treated in the pulmonary ward of RSUD Prof. H. M. Yamin, SH Pariaman from February 2–6, 2026. Assessment findings revealed dyspnea, productive cough with difficulty expectorating sputum, sleep pattern disturbances, and decreased appetite. Nursing diagnoses included ineffective airway clearance, disturbed sleep pattern, and risk for nutritional deficit. Interventions focused on respiratory monitoring, effective coughing and deep-breathing exercises, semi-Fowler positioning, sleep support, and nutritional management. After five days of care, the patient's condition improved, with reduced dyspnea, easier sputum expectoration, better sleep quality, and increased appetite. Continuous education is essential to prevent recurrence